2011
DOI: 10.1002/jmor.10921
|View full text |Cite
|
Sign up to set email alerts
|

Dry under water: Comparative morphology and functional aspects of air‐retaining insect surfaces

Abstract: Superhydrophobic surfaces prevent certain body parts of semiaquatic and aquatic insects from getting wet while submerged in water. The air layer on these surfaces can serve the insects as a physical gill. Using scanning electron microscopy, we investigated the morphology of air-retaining surfaces in five insect species with different levels of adaptation to aquatic habitats. We found surfaces with either large and sparse hairs (setae), small and dense hairs (microtrichia), or hierarchically structured surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
148
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 118 publications
(156 citation statements)
references
References 35 publications
6
148
0
Order By: Relevance
“…[24] In fact, several insects hiding or hunting underwater exploit the property of superaerophilicity. [25][26][27][28][29] Water spiders…”
Section: Doi: 101002/adma201703053mentioning
confidence: 99%
See 3 more Smart Citations
“…[24] In fact, several insects hiding or hunting underwater exploit the property of superaerophilicity. [25][26][27][28][29] Water spiders…”
Section: Doi: 101002/adma201703053mentioning
confidence: 99%
“…Reproduced with permission. [29] Copyright 2011, Wiley-VCH. d) The floating water fern salvinia with long-term air-retention properties.…”
Section: Reliable Manipulation Of Gas Bubbles By Regulating Interfacimentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid the Wenzel state, we took guidance from aquatic insects such as the water boatman Notonecta glauca, that can breathe underwater thanks to the air retention feature of their superhydrophobic hairy exoskeleton. Barthlott et al observed that while aquatic insects with long hair can support a large volume of air, insects with small hairy structures had supreme lifetime of the air film, arguing that downward progression of the air-water interface is hindered due to the fact that it costs more energy to displace an interface with a smaller radius of curvature [5]. We introduced a dual-level topography by coating a standard, micropillared substrate with nanofilaments (Fig.…”
Section: Slippery and Never Wet Features 32mentioning
confidence: 99%